Konseling Pastoral bagi Korban Kekerasan dalam Rumah Tangga di Lingkungan Gereja (Pusat Riset dan Inovasi Nasional, 2024)
Domestic violence remains a critical pastoral problem because survivors in church communities often face not only physical, psychological, sexual, and economic harm, but also spiritual narratives that may either sustain recovery or silence disclosure. This constructive qualitative study aims to formulate a Christian pastoral counseling model for survivors of domestic violence in church settings. The study applies a library-based practical-theological design by critically synthesizing peer-reviewed literature on intimate partner violence, faith-based responses, trauma- and violence-informed care, pastoral theology, Indonesian legal norms, and church-related studies. The findings show that pastoral counseling for survivors must be structured around safety rather than immediate marital reconciliation; interpret Scripture through dignity, justice, and protection of the vulnerable; recognize religious coercive control as a form of harm; integrate emotional stabilization with spiritual care; and build referral networks with psychological, legal, medical, and social services. The article proposes an integrated PASTORAL-SAFE model that combines risk assessment, survivor affirmation, trauma stabilization, theological reframing, social support, professional referral, perpetrator accountability, and long-term pastoral accompaniment. The implication is that churches need written protocols, trained pastoral teams, confidentiality standards, and collaborative safeguarding systems to prevent pastoral responses from unintentionally reproducing violence.